2017
DOI: 10.31289/biolink.v3i2.843
|View full text |Cite
|
Sign up to set email alerts
|

AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN KUNYIT (Curcuma longa LINN.) TERHADAP JAMUR Candida albicans

Abstract: The potential of Plant as one alternative medicine has been explored. One of the plants that have potential as a drug in inhibiting the fungus is a turmeric leaf. Turmeric leaf have secondary metabolite such as flavonoid, steorid, curcumin, essential oils, tannins. Secondary metabolite are thought to have the ability to inhibit the growth of the Candida albicans. Ethanol extract turmeric leaves used of concentration 10%, 20%, 30%, 40%, 50% and 60%. Each concentration after being tested to Candida albicans has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
2
1
0
5
Order By: Relevance
“…This is in line with a previous study testing the activity of C. domestica extract against the growth of Candida albicans [20]. In the study, the inhibition zone at the concentration of 20%, 40% and 60% were 2.47 mm, 4.40 mm, and 7.47 mm, respectively [20]. A study indicated that the inhibition zone against S. aureus, Gram-positive bacteria, was greater than in P. aeruginosa which is Gram-negative bacteria [7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with a previous study testing the activity of C. domestica extract against the growth of Candida albicans [20]. In the study, the inhibition zone at the concentration of 20%, 40% and 60% were 2.47 mm, 4.40 mm, and 7.47 mm, respectively [20]. A study indicated that the inhibition zone against S. aureus, Gram-positive bacteria, was greater than in P. aeruginosa which is Gram-negative bacteria [7].…”
Section: Discussionsupporting
confidence: 93%
“…Our data indicated that the inhibition zone of C. domestica extracts against P. aeruginosa increased with an increase in the concentration. This is in line with a previous study testing the activity of C. domestica extract against the growth of Candida albicans [ 20 ]. In the study, the inhibition zone at the concentration of 20%, 40% and 60% were 2.47 mm, 4.40 mm, and 7.47 mm, respectively [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The purpose of this study is to find out the activity of turmeric extract against the larvae of Aedes aegypti L. Turmeric used in the study was obtained from a farmer in the body system of larvae through the respiratory system, which will have an impact on respiratory, the larvae cannot breathe normally and will have an impact on the death of larvae (Cania & Setyaningrum, 2013;Pulungan, 2017;.…”
Section: Resultsmentioning
confidence: 99%
“…Kunyit mengandung zat aktif seperti kurkumin, minyak atsiri, fenol, flavonoid, alkaloid, terpenoid dan tanin. Kandungan metabolit sekunder tersebut diduga dapat menghambat pertumbuhan mikroba (3) . Untuk memastikan kunyit sebagai antimikroba yang dapat memperpanjang umur simpan produk, maka dilakukanlah penelitian pendugaan umur simpan terhadap minuman sari kunyit.…”
Section: Pendahuluan Latar Belakangunclassified